Konsep Kematian dalam Perspektif Agama Buddha Theravada - Azisi, Ali Mursyid (AL-ADYAN, 2021)
This article examines the concept of death in the Theravada Buddhist perspective. Where the teachings show the stages in addressing or even the state after death. When facing death in Theravada Buddhism, it is very fearful to avoid fear and doubt, instead you have to be happy by preparing for life's good deeds. The existence of punarbawa / rebirth is one of the concepts carried on as a hereditary belief from Buddhist scriptures. By using a qualitative approach in analyzing, analyzing data from relevant literature / literature studies, so that they can be arranged with related material. This article is important to study further, by looking at how the perspective implanted in Theravada Buddhism, especially the concept of death, will be a source of knowledge which will become a source of insight and learning. The goal is a category that can be consumed by scientific studies of religious studies and academics or the general public related to themes that are expected to be useful for many circles. That way the purpose of life in every religion is the goal of others and still instills virtue.